1982
DOI: 10.1161/01.res.50.1.86
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical interactions between four heart chambers with and without the pericardium in canine hearts.

Abstract: By using excised postmortem hearts obtained from 15 mongrel dogs with the pericardium intact, we investigated mechanical interactions between the four heart chambers from the standpoint of ventricular pressure-volume relationships. The interactions investigated were those between (1) the atrium and the ventricle, (2) the right ventricle and left ventricles, (3) the atrium and one ventricle vs. the other ventricle, and finally (4) the left and right atrium and the right ventricle vs. the left ventricle. For the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(38 citation statements)
references
References 50 publications
2
36
0
Order By: Relevance
“…First, we compared the pre-and post-pericardiectomy pressure-time curves graphically. Second, we analyzed the relative contribution of the pericardium to chamber pressures in both sides of the heart by selecting prepericardiectomy chamber pressures of interest: 1, 3, 5, 8, 11, and 15 mmHgintherightheartand2, 5,8,11,15,20, and 25 mm Hg in the left heart. We then computed the pressure drop caused by pericardiectomy at the volumes obtained at these prepericardiectomy pressures.…”
Section: Methodsmentioning
confidence: 99%
“…First, we compared the pre-and post-pericardiectomy pressure-time curves graphically. Second, we analyzed the relative contribution of the pericardium to chamber pressures in both sides of the heart by selecting prepericardiectomy chamber pressures of interest: 1, 3, 5, 8, 11, and 15 mmHgintherightheartand2, 5,8,11,15,20, and 25 mm Hg in the left heart. We then computed the pressure drop caused by pericardiectomy at the volumes obtained at these prepericardiectomy pressures.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, when both ventricles eject blood during systole, both atria become larger due to the concomitant increase in venous return. In an in vitro study, Maruyama et al (1982) showed that atrial distention elevated left ventricular pressure at any given volume with the pericardium intact. Thus, there is a possibility that the pericardial restraint on the heart becomes welldefined at end systole in acute ischemia because of the increase in blood containing structures in the pericardial sac caused by the systolic dysfunction of the left ventricle.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanical interactions between the left ventricle and other cardiac structures, which may be supposed to occur in vivo, are small, if any, in the present study because we removed the pericardium, the right ventricle, and a part of the right atrium (Maruyama et al 1982a). Thus, left ventricular diastolic compliance might not have been changed through the intervention study, indicating that left ventricular end-diastolic volume is constant under constant left ventricular end-diastolic pressure.…”
Section: Methodological Considerationsmentioning
confidence: 95%